df-Statistical Convergence of Order ? and df-Strong Cesaro Summability of Order ? in Accordance to a Modulus in Metric Spaces - Colak, Rifat; Kayan, Emine (Chiang Mai Univ, Fac Science, 2022)
In the current study we present df-statistical convergence of order alpha and df-strong Cesaro summability of order alpha in accordance to a modulus for a sequence in a metric space. Furthermore we introduce the connections between the sets of df-statistically convergent sequences of order alpha and between the sets of df-strongly Cesaro summable sequences of order alpha in accordance to a modulus for various values alpha and under some conditions on f. Besides this we introduce the relationships between the set of df-statistically convergent sequences of order alpha and the set of df-strongly Cesaro summable sequences of order alpha in accordance to a modulus for various values alpha and under some conditions on f.
Keywords: alpha-density; modulus function; statistical convergence; strong Cesaro summability